Resin-based composite material for improving wear resistance of PVC (polyvinyl chloride) hose and preparation method of resin-based composite material

By combining tetraaminophthalocyanine copper-functionalized molybdenum disulfide nanoparticles with polyimide microspheres, a self-lubricating protective layer was constructed, which solved the problem of insufficient wear resistance of PVC hoses and achieved a significant improvement in the wear resistance and mechanical properties of the material.

CN119285943APending Publication Date: 2025-01-10ZHEJIANG HUTIAN RUBBER BELT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411500006.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing PVC hoses have poor wear resistance, insufficient bonding strength between the filler and the substrate, making them prone to detachment, and poor dispersion, resulting in uneven wear resistance.

Method used

A self-lubricating protective layer is constructed by combining tetraaminophthalocyanine copper-functionalized molybdenum disulfide nanoparticles with polyimide microspheres. The composite structure of phthalocyanine copper and molybdenum disulfide nanoparticles prevents agglomeration, enhances the bonding strength with the PVC matrix, and builds a robust protective layer on the surface of the polyimide microspheres.

Benefits of technology

It significantly improves the wear resistance of PVC hoses, reduces friction, prevents the agglomeration of nano-molybdenum disulfide, enhances the overall wear resistance and mechanical properties of the material, reduces the wear rate, and improves the bonding strength with the PVC matrix.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285943A_ABST
    Figure CN119285943A_ABST
Patent Text Reader

Abstract

The invention discloses a resin-based composite material for improving wear resistance of a PVC (polyvinyl chloride) hose and a preparation method of the resin-based composite material, and belongs to the technical field of wear-resistant materials for PVC hoses. The copper tetraamino phthalocyanine and the nano molybdenum disulfide are compounded, so that the nano molybdenum disulfide is prevented from being agglomerated, the nano molybdenum disulfide plays a stable lubricating role, the friction force and the abrasion probability are reduced, and the surface adhesion of the material is reduced through the surface lubricating role. The rigid structure of the polyimide microspheres provides support for the nano molybdenum disulfide, and the wear resistance is enhanced. 2-(4-pyrimidine) dicarboxaldehyde and copper tetraamino phthalocyanine are subjected to a Schiff base reaction, a protective layer is constructed on the surface of the polyimide microsphere, additional mechanical support is provided, polyimide particles are prevented from being agglomerated, and the bonding strength with a PVC matrix and the overall wear resistance are improved. The Schiff base structure reduces interfacial tension, enables molecular chains to stretch, facilitates interpenetration of polyimide among PVC molecular chains and firm inlaying of polyimide in a system, prevents particles from falling off, avoids aggravated wear, and can absorb and disperse friction force microcosmically and protect a PVC matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PVC hose wear-resistant materials, and in particular relates to a resin-based composite material for improving the wear resistance of a PVC hose and a preparation method thereof. Background Art

[0002] PVC hose, or polyvinyl chloride hose, is a flexible pipe made by adding plasticizers, stabilizers and other additives to polyvinyl chloride resin through extrusion molding and other processes. PVC material itself has good chemical stability, corrosion resistance and certain mechanical properties. After being made into a hose, it can be used in a variety of environments. PVC pipes have the characteristics of strong corrosion resistance, high strength and good rigidity. Therefore, they are widely used in technical fields such as water supply, building drainage, sewage, and chemical industry. However, due to the general wear resistance of PVC pipes, the application of PVC pipes in the field is greatly affected. Therefore, it is necessary to improve its wear resistance by adding fillers.

[0003] However, there are some defects in improving the wear resistance of PVC hoses by adding fillers. The bonding strength between the filler and the PVC substrate is poor, and it is easy to fall off during use, and it cannot continue to play the role of improving the wear resistance. These fillers may affect other properties of PVC hoses, such as chemical stability and flexibility. In addition, the dispersion of the filler may also be poor, and it is easy to agglomerate, resulting in uneven wear resistance. Therefore, it is very important to prepare suitable materials to reduce the friction and wear probability of PVC hoses, prevent agglomeration, and improve the bonding strength with the PVC matrix. Summary of the invention

[0004] In view of the above situation, in order to overcome the defects of the prior art, the resin-based composite material prepared by the present invention achieves the effects of enhancing the self-lubricating property of the composite material, preventing the agglomeration of nano-molybdenum disulfide, and constructing a solid protective layer, thereby significantly improving the wear resistance of the PVC hose.

[0005] In order to achieve the above object, the following technical scheme is adopted: On the one hand, the present invention provides a method for preparing a resin-based composite material for improving the wear resistance of a PVC hose, comprising the following steps:

[0006] S1, adding copper tetraaminophthalocyanine to DMF, dissolving to obtain copper tetraaminophthalocyanine solution, adding nano molybdenum disulfide to DMF, ultrasonically dispersing for 10 minutes to obtain nano molybdenum disulfide dispersion, adding the copper tetraaminophthalocyanine solution to the nano molybdenum disulfide dispersion, stirring continuously, standing for 12 hours and then filtering, then drying at 120° C. for 12 hours, and then placing in a muffle furnace at 500° C. for 3 hours to obtain copper phthalocyanine functionalized nano molybdenum disulfide;

[0007] S2. Dissolve the diamine monomer in DMF under a nitrogen atmosphere, then add the dianhydride monomer to the solution in small batches and multiple times, then add a surfactant, react at room temperature for 12 hours to obtain a polyamic acid solution, add phthalocyanine functionalized nano molybdenum disulfide to DMF to obtain a two-component modified liquid, add the two-component modified liquid to the polyamic acid solution, transfer to a reactor, hydrothermally react at 130-280° C. for 5 hours, take out and cool to room temperature, add 2-(4-pyrimidine)diformaldehyde, ultrasonicate for 30 minutes, filter, wash the obtained solid with deionized water, and dry at 120° C. for 12 hours to obtain modified polyimide microspheres, i.e., the resin-based composite material.

[0008] Furthermore, the mass ratio of copper tetraaminophthalocyanine to DMF in the copper tetraaminophthalocyanine solution is 0.8-1.2:150-250.

[0009] Furthermore, the mass ratio of nano-molybdenum disulfide to DMF in the nano-molybdenum disulfide dispersion is 0.8-1.2:100-180.

[0010] Furthermore, in step S1, the mass ratio of the tetraaminophthalocyanine copper solution to the nano-molybdenum disulfide dispersion is 1.5-2.5:2.5-3.5.

[0011] Furthermore, the mass ratio of the diamine monomer, DMF, dianhydride monomer and surfactant in the polyamic acid solution is 1-1.5:100-180:0.8-0.95:0.5-1.

[0012] Furthermore, the mass ratio of phthalocyanine functionalized nano-molybdenum disulfide to DMF in the two-component modified liquid is 0.8-1.2:90-110.

[0013] Furthermore, in step S2, the mass ratio of the two-component modified liquid to the polyamic acid solution is 0.8-1.2:2-3.2.

[0014] Furthermore, the diamine monomer is one of ethylenediamine, p-phenylenediamine and 4,4'-diaminodiphenylmethane, and the dianhydride monomer is one of 4,4'-oxydiphthalic anhydride, pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 4,4'-p-phenylenedioxydiphthalic anhydride and bisphenol A dianhydride.

[0015] Furthermore, the surfactant is a combination of one or more of Span60, Span80, Span85, Tween60 and Tween80.

[0016] On the other hand, the present invention also provides a resin-based composite material for improving the wear resistance of a PVC hose, which is prepared by the above-mentioned preparation method.

[0017] The beneficial effects of the present invention are:

[0018] (1) The present invention greatly enhances the self-lubricating property of the composite material by functionalizing with copper phthalocyanine, which can significantly reduce friction and the probability of wear. Surface lubrication can reduce the surface adhesion of the material, making the PVC hose suitable for liquid transportation. The composite structure of copper tetraaminophthalocyanine and nano-molybdenum disulfide prevents the agglomeration of nano-molybdenum disulfide. The uniformly dispersed nano-molybdenum disulfide can play a stable lubricating role in the entire material system, bear part of the friction, and reduce the wear on the polyimide microspheres and the PVC matrix. At the same time, the rigid structure of the polyimide microspheres provides support for the nano-molybdenum disulfide, enhancing the wear resistance.

[0019] (2) Through the Schiff base reaction between 2-(4-pyrimidine) dicarboxaldehyde and tetraaminophthalocyanine copper, a strong and stable protective layer is constructed on the surface of polyimide microspheres. The protective layer provides additional support for the polyimide microspheres in terms of mechanical properties, prevents polyimide particles from agglomerating, improves the bonding strength with the PVC matrix, and enhances the overall wear resistance of the material. The Schiff base network structure limits the excessive movement of the polyimide molecular chain, allowing it to maintain a relatively stable conformation. The network structure also has anisotropic thermal conductivity, which can transfer and conduct frictional heat and prevent local thermal stress. The Schiff base structure and the imino groups on the polyimide molecular chain After agglomeration, the interfacial tension between polyimide and PVC matrix is ​​reduced, the molecular chain is stretched, which is conducive to the interpenetration of polyimide between PVC molecular chains, increasing the contact area, and making the modified polyimide microspheres firmly embedded in the PVC system. When the PVC hose is subjected to external force, during the wear process, good interfacial bonding can prevent the polyimide particles from falling off and avoid the formation of abrasive particles to aggravate the wear. At the microscopic level, when the friction pair contacts the material surface, the polyimide microspheres and nano-molybdenum disulfide can absorb and disperse the friction force by deformation, displacement, etc., protecting the PVC matrix from severe wear. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The friction performance test results of various embodiments and comparative examples of the present invention are shown in FIG.

[0021] Figure 2 The wear performance test results of various embodiments and comparative examples of the present invention are shown in FIG.

[0022] Figure 3 The SEM images of the wear surfaces of the embodiments and comparative examples of the present invention are shown in FIG.

[0023] Figure 4 The following are the mechanical property test results of various embodiments and comparative examples of the present invention.

[0024] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0027] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0028] Example 1

[0029] A method for preparing a resin-based composite material for improving the wear resistance of a PVC hose comprises the following steps:

[0030] S1, adding copper tetraaminophthalocyanine to DMF, dissolving to obtain copper tetraaminophthalocyanine solution, adding nano molybdenum disulfide to DMF, ultrasonically dispersing for 10 minutes to obtain nano molybdenum disulfide dispersion, adding the copper tetraaminophthalocyanine solution to the nano molybdenum disulfide dispersion, stirring continuously, standing for 12 hours and then filtering, then drying at 120° C. for 12 hours, and then placing in a muffle furnace at 500° C. for 3 hours to obtain copper phthalocyanine functionalized nano molybdenum disulfide;

[0031] S2. Dissolve the diamine monomer in DMF under a nitrogen atmosphere, then add the dianhydride monomer to the solution in small batches and multiple times, then add a surfactant, react at room temperature for 12 hours to obtain a polyamic acid solution, add phthalocyanine functionalized nano molybdenum disulfide to DMF to obtain a two-component modified liquid, add the two-component modified liquid to the polyamic acid solution, transfer to a reactor, hydrothermally react at 130-280° C. for 5 hours, take out and cool to room temperature, add 2-(4-pyrimidine)diformaldehyde, ultrasonicate for 30 minutes, filter, wash the obtained solid with deionized water, and dry at 120° C. for 12 hours to obtain modified polyimide microspheres, i.e., the resin-based composite material.

[0032] The mass ratio of copper tetraaminophthalocyanine to DMF in the copper tetraaminophthalocyanine solution is 0.8 g:150 mL; the mass ratio of nano molybdenum disulfide to DMF in the nano molybdenum disulfide dispersion is 0.8 g:100 mL; the mass ratio of copper tetraaminophthalocyanine solution to nano molybdenum disulfide dispersion in step S1 is 1.5:2.5; the mass ratio of diamine monomer, DMF, dianhydride monomer and surfactant in the polyamic acid solution is 1:100:0.8:0.5; the mass ratio of phthalocyanine functionalized nano molybdenum disulfide to DMF in the two-component modified solution is 0.8:90; the mass ratio of the two-component modified solution to the polyamic acid solution in step S2 is 0.8:2; the diamine monomer is ethylenediamine, the dianhydride monomer is 4,4'-oxydiphthalic anhydride; and the surfactant is Span60.

[0033] Example 2

[0034] A method for preparing a resin-based composite material for improving the wear resistance of a PVC hose comprises the same steps as those in Example 1.

[0035] The mass ratio of copper tetraaminophthalocyanine to DMF in the copper tetraaminophthalocyanine solution is 1.2:250; the mass ratio of nano molybdenum disulfide to DMF in the nano molybdenum disulfide dispersion is 1.2:180; the mass ratio of copper tetraaminophthalocyanine solution to nano molybdenum disulfide dispersion in step S1 is 2.5:3.5; the mass ratio of diamine monomer, DMF, dianhydride monomer and surfactant in the polyamic acid solution is 1.5:180:0.95:1; the mass ratio of phthalocyanine functionalized nano molybdenum disulfide to DMF in the two-component modified solution is 1.2:110; the mass ratio of the two-component modified solution to the polyamic acid solution in step S2 is 1.2:3.2; the diamine monomer is p-phenylenediamine, the dianhydride monomer is pyromellitic anhydride; and the surfactant is Span80.

[0036] Example 3

[0037] A method for preparing a resin-based composite material for improving the wear resistance of a PVC hose comprises the same steps as those in Example 1.

[0038] The mass ratio of copper tetraaminophthalocyanine to DMF in the copper tetraaminophthalocyanine solution is 1g:180; the mass ratio of nano molybdenum disulfide to DMF in the nano molybdenum disulfide dispersion is 1g:150mL; the mass ratio of copper tetraaminophthalocyanine solution to nano molybdenum disulfide dispersion in step S1 is 2:3; the mass ratio of diamine monomer, DMF, dianhydride monomer and surfactant in the polyamic acid solution is 1.2:150:0.85:0.6; the mass ratio of phthalocyanine functionalized nano molybdenum disulfide to DMF in the two-component modified solution is 1:100; the mass ratio of the two-component modified solution to the polyamic acid solution in step S2 is 1:2.5; the diamine monomer is 4,4'-diaminodiphenylmethane, the dianhydride monomer is 3,3',4,4'-biphenyltetracarboxylic dianhydride; the surfactant Tween60.

[0039] Example 4

[0040] A method for preparing a resin-based composite material for improving the wear resistance of PVC hose

[0041] In this embodiment, the dianhydride monomer is 4,4'-diphenylenedioxydiphthalic anhydride; the surfactant is a combination of Span60, Span85 and Tween80 in a ratio of 3:4:8, and the rest is the same as in Embodiment 3.

[0042] Comparative Example 1

[0043] The difference between this comparative example and Example 1 is that the resin-based composite material is unmodified polyimide microspheres, and the rest is the same as Example 4.

[0044] The resin-based composite material is prepared by the following steps: dissolving a diamine monomer in DMF under a nitrogen atmosphere, then adding a dianhydride monomer to the solution in small batches for multiple times, then adding a surfactant, reacting at room temperature for 12 hours to obtain a polyamic acid solution, transferring it to a reactor, hydrothermally reacting it at 150° C. for 5 hours, filtering it, washing the obtained solid with deionized water, and drying it at 120° C. for 12 hours to obtain polyimide microspheres, namely the resin-based composite material.

[0045] Comparative Example 2

[0046] The difference between this comparative example and Example 1 is that the nano-molybdenum disulfide is not functionalized with copper phthalocyanine in the preparation of the resin-based composite material, that is, an equal amount of nano-molybdenum disulfide is used instead of copper phthalocyanine functionalized nano-molybdenum disulfide, and the rest is the same as Example 4.

[0047] Comparative Example 3

[0048] The difference between this comparative example and Example 1 is that 2-(4-pyrimidine)dicarboxaldehyde is not contained in the preparation of the resin-based composite material, and the rest is the same as Example 4.

[0049] Results Analysis

[0050] A PVC hose was obtained by extrusion, cooling, pulling and cutting of the following components through a twin-screw granulator: 100 parts of PVC resin, 8 parts of the resin-based composite material of the embodiment and the comparative example, 3 parts of a calcium zinc stabilizer, 15 parts of calcium stearate, 5 parts of high-density polyethylene wax and 3 parts of dioctyl phthalate; the obtained PVC hose was subjected to the following performance analysis.

[0051] Test Example 1

[0052] Friction performance test

[0053] The friction coefficients of the embodiments and comparative examples of the present invention in a dry friction environment were tested by an MPX-2000 friction machine. Figure 1 .

[0054] Depend on Figure 1 The results show that the friction coefficients of Examples 1-4 are significantly lower than those of the comparative examples, indicating that the resin-based composite material of the present invention can greatly enhance the self-lubricating property of the PVC hose. The reason is that the functional combination of copper tetraaminophthalocyanine and nano-molybdenum disulfide prevents the agglomeration of nano-molybdenum disulfide. The uniformly dispersed nano-molybdenum disulfide plays a stable lubricating role in the material system and bears part of the friction force, thereby reducing the friction coefficient. Comparative Example 1 is an unmodified polyimide microsphere. Since there is no functional combination of copper tetraaminophthalocyanine and nano-molybdenum disulfide and 2-(4-pyrimidine ) The protective layer constructed by diformaldehyde has a high friction coefficient. Without the lubricating effect of nano-molybdenum disulfide and the support of the protective layer, the material surface is more likely to generate greater friction. In Comparative Example 2, nano-molybdenum disulfide is not functionalized with copper phthalocyanine, and an equal amount of nano-molybdenum disulfide is used instead of copper phthalocyanine functionalized nano-molybdenum disulfide. At this time, nano-molybdenum disulfide is easy to agglomerate and cannot be evenly dispersed to play a lubricating role, resulting in an increase in the friction coefficient. Comparative Example 3 does not contain 2-(4-pyrimidine) diformaldehyde, and a protective layer cannot be constructed, which reduces the surface lubrication performance of the material and increases the friction coefficient.

[0055] Test Example 2

[0056] Wear performance test

[0057] The wear amount of each embodiment of the present invention and the comparative example in a dry friction environment was tested by an MPX-2000 friction machine. The results are shown in Figure 2 .

[0058] The SEM analysis of the wear surfaces of the embodiments of the present invention and the comparative examples was performed by scanning electron microscopy. The results are shown in Figure 3 .

[0059] The results show that the wear rates of Examples 1-4 are lower than those of the comparative examples, and it can be seen from the SEM images that the wear surfaces of the examples are relatively smooth, while the wear surfaces of the comparative examples are relatively rough. This is because the rigid structure of the polyimide microspheres in the present invention provides support for nano-molybdenum disulfide, thereby enhancing the wear resistance. At the same time, the protective layer constructed by 2-(4-pyrimidine)dicarboxaldehyde and tetraaminophthalocyanine copper on the surface of the polyimide microspheres improves the bonding strength with the PVC matrix, prevents the polyimide particles from falling off, and avoids the formation of abrasive particles that aggravate wear. In Comparative Example 1, the unmodified polyimide microspheres lack the lubrication, support, and protective layer of nano-molybdenum disulfide. During the wear process, the polyimide microspheres are easy to agglomerate, not tightly bonded to the PVC matrix, and easily fall off to form abrasive particles, thereby aggravating the wear, resulting in a high wear rate and a rough wear surface. In Comparative Example 2, since the nano-molybdenum disulfide is not functionalized, it is easy to agglomerate and cannot play a stable lubricating role in the entire material system, and cannot effectively reduce the wear of the polyimide microspheres and the PVC matrix, and the wear rate increases. Comparative Example 3 lacks a protective layer constructed of 2-(4-pyrimidine)dicarboxaldehyde. The polyimide particles are easy to agglomerate and have low bonding strength with the PVC matrix. They are easy to fall off during the wear process, resulting in an increased wear rate and a rough wear surface.

[0060] Test Example 3

[0061] Mechanical properties test

[0062] The tensile strength and impact strength of each embodiment of the invention and the comparative example were tested by TH6003 plastic pipe pressure testing machine. The results are shown in Figure 4 .

[0063] Figure 4 The results show that the mechanical properties of Examples 1-4 are better than those of the comparative example. In the resin-based composite material of the present invention, the composite structure of copper tetraaminophthalocyanine and nano-molybdenum disulfide and the construction of the protective layer not only enhance the wear resistance of the material, but also provide additional support for the polyimide microspheres in terms of mechanical properties, restrict the excessive movement of the polyimide molecular chain, keep it in a relatively stable conformation, and increase the contact area between the polyimide and the PVC matrix, so that the modified polyimide microspheres are firmly embedded in the PVC system, thereby improving the tensile strength and impact strength of the material. The unmodified polyimide microspheres have not undergone functionalization treatment and protective layer construction, and their bonding strength with the PVC matrix is ​​low. They are easily separated when subjected to force, resulting in poor mechanical properties, low tensile strength and impact strength. The unfunctionalized nano-molybdenum disulfide in Comparative Example 2 cannot provide effective support for the polyimide microspheres, and also affects the bonding of polyimide to the PVC matrix, resulting in a decrease in mechanical properties. Comparative Example 3 lacks a protective layer, and the polyimide molecular chain moves more freely and cannot maintain a stable conformation. It is also not tightly bonded to the PVC matrix, resulting in reduced mechanical properties.

[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0065] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a resin-based composite material for improving the wear resistance of a PVC hose, characterized in that: The following steps are involved: S1, adding copper tetraaminophthalocyanine to DMF, dissolving to obtain copper tetraaminophthalocyanine solution, adding nano molybdenum disulfide to DMF, ultrasonically dispersing for 10 minutes to obtain nano molybdenum disulfide dispersion, adding the copper tetraaminophthalocyanine solution to the nano molybdenum disulfide dispersion, stirring continuously, standing for 12 hours and then filtering, then drying at 120° C. for 12 hours, and then placing in a muffle furnace at 500° C. for 3 hours to obtain copper phthalocyanine functionalized nano molybdenum disulfide; S2. Dissolve the diamine monomer in DMF under a nitrogen atmosphere, then add the dianhydride monomer to the solution in small batches and multiple times, then add a surfactant, react at room temperature for 12 hours to obtain a polyamic acid solution, add phthalocyanine functionalized nano molybdenum disulfide to DMF to obtain a two-component modified liquid, add the two-component modified liquid to the polyamic acid solution, transfer to a reactor, hydrothermally react at 130-280° C. for 5 hours, take out and cool to room temperature, add 2-(4-pyrimidine)diformaldehyde, ultrasonicate for 30 minutes, filter, wash the obtained solid with deionized water, and dry at 120° C. for 12 hours to obtain modified polyimide microspheres, i.e., the resin-based composite material.

2. The method for preparing a resin-based composite material for improving the wear resistance of a PVC hose according to claim 1, characterized in that: The mass ratio of copper tetraaminophthalocyanine to DMF in the copper tetraaminophthalocyanine solution is 0.8-1.2:150-250.

3. The method for preparing a resin-based composite material for improving the wear resistance of a PVC hose according to claim 2, characterized in that: The mass ratio of nano-molybdenum disulfide to DMF in the nano-molybdenum disulfide dispersion is 0.8-1.2:100-180.

4. The method for preparing a resin-based composite material for improving the wear resistance of a PVC hose according to claim 3, characterized in that: In the step S1, the mass ratio of the tetraaminophthalocyanine copper solution to the nano-molybdenum disulfide dispersion is 1.5-2.5:2.5-3.

5.

5. The method for preparing a resin-based composite material for improving the wear resistance of a PVC hose according to claim 4, characterized in that: The mass ratio of the diamine monomer, DMF, dianhydride monomer and surfactant in the polyamic acid solution is 1-1.5:100-180:0.8-0.95:0.5-1.

6. The method for preparing a resin-based composite material for improving the wear resistance of a PVC hose according to claim 5, characterized in that: The mass ratio of phthalocyanine functionalized nano molybdenum disulfide to DMF in the two-component modified liquid is 0.8-1.2:90-110.

7. The method for preparing a resin-based composite material for improving the wear resistance of a PVC hose according to claim 6, characterized in that: In the step S2, the mass ratio of the two-component modified liquid to the polyamic acid solution is 0.8-1.2:2-3.

2.

8. A method for preparing a resin-based composite material for improving the wear resistance of a PVC hose according to claim 7, characterized in that: The diamine monomer is one of ethylenediamine, p-phenylenediamine and 4,4'-diaminodiphenylmethane, and the dianhydride monomer is one of 4,4'-oxydiphthalic anhydride, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-p-phenylenedioxydiphthalic anhydride and bisphenol A dianhydride.

9. The method for preparing a resin-based composite material for improving the wear resistance of a PVC hose according to claim 8, characterized in that: The surfactant is a combination of one or more of Span60, Span80, Span85, Tween60 and Tween80.

10. A resin-based composite material for improving the wear resistance of a PVC hose, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 9.